PERBANDINGAN RUMUSAN TINDAK PIDANA HOMOSEKSUAL DALAM HUKUM ISLAM DAN KUHP INDONESIA - Zul Anwar Ajim (Yurisprudentia: Jurnal Hukum Ekonomi, 2016)
This study is started from a happening global phenomenon which is the occurrence of understanding about lesbians, gay, bisexual and transgender (LGBT) are growing up rapidly.  These understandings make some differences that affect to the doer status either crime or character deviance. Some law system considers it as a sexual deviance so that it is not a crime. Whereas Islamic law says that it is a crime. In Islamic law system, homosexual is a serious criminal offence, so that big punishment should be given on the doer himself that is capital punishment. Meanwhile, in KUHP stated that homosexual is misdemeanor as adultery with maximum 5 year imprisonment.